Designing Ergonomic Study Chair Using Quality Function Deployment Method with Anthropometry Approach - Luthfini Lubis , Arina; Vivi Putri, Meylia (KnE Life Sciences, 2020)
Increasing the high number of under-fives entering the age of study, commonly called early childhood education (Pendidikan Anak Usia Dini–PAUD), creates an opportunity to design a product that supports learning activities for the toddlers, namely folding study desks. This research aims to make a redesign of folding table-chair products specially designed for toddlers by considering ergonomic aspects that prioritize function and comfort using Quality Function Deployment (QFD) method through anthropometry approach of toddler’s body. This study focuses on toddlers aged 3 yr to 5 yr who are students of the playing group and kindergarten at Integrated Islamic Kindergarten (Taman Kanak-kanak Islam Terpadu-TKIT) “Rabbani”. Different body sizes of toddlers with adults are the main consideration in determining anthropometric approach, but it is also expected to produce ergonomic products both in terms of materials and product size to a child’s sitting position. The results of this study obtained a comfortable chair table, soft and comfortable backrest, strong seat resistance, comfortable padded seat cushion, has a place to store bag/footrest, has a place to store stationery, has an attractive color and seats safe to use, and has additional features for gadget. As for the changes made in terms of the dimensions of the chair that prioritize ergonomic values, the seat height is 60 mm, the back height is 33.2 mm, the width of the backrest is 30 mm, the length of the seat is 26.6 mm, and the seat width is 26.6 mm. All these additions are additional tolerance for comfort, especially for large children. Keywords: ergonomic product design; quality function deployment; toddler study chair design